Improving Digital Promotion of MSMEs Through Personal Mentoring-Based Canva Training in Mata Air Village - Mukhibatul Hikmah; Gidion Juanri Toding (PT. TAKAZA INNOVATIX LABS, 2026)
Indonesian rural Micro, Small, and Medium Enterprises (MSMEs) face intense digital competition due to limited promotional skills and low content marketing literacy, particularly in Mata Air Village, East Kutai. This community service program aims to improve MSME digital promotion through personalized Canva training within the Village Development Program. A qualitative ABCD approach was applied, encompassing problem mapping, program design, and direct mentoring for 10 purposive sample MSMEs from a population of 20-30 active businesses. Data instruments included participant observation, in-depth interviews, and Canva template documentation, analyzed descriptively using SWOT and triangulation. Results showed participants mastered the drag-and-drop feature for product packaging and social media content design, despite internet connection constraints. In conclusion, the Canva training successfully developed independent design skills, increased promotional efficiency, and increased competitiveness against e-commerce platforms.